Occupational Tasks Influencing Lung Function and Respiratory Symptoms Among Charcoal-Production Workers: A Time-Series Study - Pramchoo, Walaiporn (Saf Health Work, 2017)
BACKGROUND: Tasks involved in traditional charcoal production expose workers to various levels of charcoal dust and wood smoke. This study aimed to identify specific tasks influencing lung function and respiratory symptoms. METHODS: Interviews, direct observation, and task/symptom checklists were used to collect data from 50 charcoal-production workers on 3 nonwork days followed by 11 workdays. The peak expiratory flow rate (PEFR) was measured four times per day. RESULTS: The PEFR was reduced and the prevalence of respiratory symptoms increased over the first 6–7 workdays. The PEFR increased until evening on nonwork days but not on workdays. Loading the kiln and collecting charcoal from within the kiln markedly reduced the PEFR and increased the odds of respiratory symptoms. CONCLUSION: Tasks involving entry into the kiln were strongly associated with a short-term drop in the PEFR and the occurrence of respiratory symptoms, suggesting a need for the use of protective equipment and/or the operation of an effective kiln ventilation system.